Calibration and adjustments of degree‐1 and ‐2 re‐entrant turnstile circulators using a partially recessed quarter‐wave long dielectric resonator. Issue 1 (1st January 2016) - Helszajn, Joseph; Carignan, Louis‐Philippe; Sharp, John
Abstract : The choice of reference planes in the design of the turnstile circulator is not unique. The purpose of this study is to examine two possibilities each of which is equally valid and experimentally verified. One possible arrangement is obtained by replacing the resonator region by a metallic post across the waveguide. The other employs a short‐circuit plate tangential to the circumference of the resonator. The main difference between the two solutions is the gap between the open flat face of the resonator and the in‐phase piston. The prototype used for this purpose is a novel partially recessed quarter‐wave long resonator in half‐height waveguide. This study includes the development of a degree‐2 circulator using such a junction.